MOF material, preparation method and application thereof, and CO2 adsorbent
By using mixed solutions of neutral ligand, hydrogen bond acceptor and hydrogen bond donor in the synthesis process of MOF materials, combined with mixed solutions of metal salts and linkers and heat treatment, MOF materials with highly adjustable structural properties were prepared, which solved the efficiency of existing MOF materials in CO2 adsorption and large-scale applications, and achieved efficient CO2 adsorption and good stability.
Patent Information
- Application Number
- CN202411915517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing MOF materials require the use of costly and corrosive regulators during the synthesis process, and their microporous structure leads to a reduced mass transfer rate in the adsorption process, limiting their efficiency in CO2 adsorption and large-scale applications.
By formulating a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor, and a second mixed solution of a metal salt and a linker, combined with the use of a heat treatment and the use of a regulator, a MOF material with a highly adjustable structural performance is prepared. This method is highly regulated in terms of surface area, pore volume, average pore size, etc., and retains additional metal sites and acid/basic sites, significantly increasing the adsorption amount of CO2.
The efficient preparation of MOF materials was achieved, and the adsorption amount of CO2 was significantly improved. Compared with traditional UiO-66 materials, the adsorption amount was increased by nearly 300%. The material showed good stability and regeneration performance in the circulating CO2 adsorption-desorption experiment.
Smart Images

Figure CN119798690A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal organic composite material synthesis, and in particular to a MOF material and a preparation method and application thereof, and a CO2 adsorbent. Background Art
[0002] Due to the large-scale combustion of fossil fuels, the concentration of carbon dioxide in the atmosphere continues to rise, breaking the original heat balance of the earth system. The earth's climate system has undergone significant changes characterized by warming, which has brought adverse effects on the natural environment and also brought troubles to human society. In order to control its further expansion, carbon capture and storage (CCS) technology is one of the widely used CO2 removal methods. This technology separates the CO2 produced by the industrial and energy industries through carbon capture technology, and then transports and seals it to places isolated from the atmosphere such as the seabed or underground through carbon storage methods. In carbon capture technology, CO2 adsorption is considered to be one of the most effective methods. The main principle is to capture CO2 molecules in porous materials using host-guest interactions.
[0003] Metal organic frameworks (MOFs) and their composites are a relatively new class of porous materials that can be used for the adsorption and capture of a variety of gases. MOFs materials are coordination polymers self-assembled from multidentate organic ligands containing oxygen, nitrogen, etc. (mostly aromatic polyacids and polybases) and transition metal ions. They have many properties such as porosity, large specific surface area and multiple metal sites. Therefore, they have many applications in the field of chemistry and chemical engineering, such as gas storage, molecular separation, catalysis, and drug sustained release. There are many methods for preparing MOFs materials, the most common of which are hydrothermal method, solvothermal method, vapor deposition method, sol-gel method, template method, etc. In the synthesis process, metal ions and organic ligands are assembled using specific solvents, sols or templates according to different principles, and regulators such as structure directing agents and pore expanders are added to adjust the morphology and crystal structure of the material.
[0004] Among all MOFs materials, UiO-66, as a zirconium prototype adsorption material, has broad application prospects due to its good hydrothermal stability, chemical stability, high specific surface area and easily adjustable surface properties. UiO-66 is a rigid metal organic framework material with Zr as the metal center and terephthalic acid as the organic ligand. Its easily adjustable physical and chemical properties make its synthesis more flexible in different environments, and it is usually crystallized by solvothermal methods. However, because the synthesis process of UiO-66 is usually carried out under high temperature (140-240°C), it is necessary to use costly and corrosive regulators to change its crystallization system and coordination environment during the synthesis process, which limits its large-scale application.
[0005] Most metal organic framework materials reported so far have microporous structures, and the microporous nature will lead to slower diffusion of molecules in the adsorption process and lower mass transfer rate. In addition, the low availability of its acidic and basic sites hinders its diffusion process of CO2 under low pressure conditions, thereby limiting its conversion into higher value-added products. In recent years, mesoporous metal organic framework materials with nanoscale pore structures have attracted widespread attention and have shown great potential in gas storage, adsorption, heterogeneous catalysis, molecular sensing, etc. At present, the methods for synthesizing mesoporous structures in microporous structures mainly include solvent evaporation diffusion method, microwave-assisted synthesis, ionic liquid / supercritical CO2 emulsion method, metal-ligand-fragment co-assembly method, subsequent etching strategy, modulator-induced defect formation strategy, etc. Most of the above methods are often complicated and require some additional steps to remove the template, which will lead to bond breakage in its mesoporous structure and further reduce its adsorption performance. Therefore, it is urgent to provide a preparation method of MOF materials to solve the above problems. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a MOF material and a preparation method and application thereof, and a CO2 adsorbent. The MOF material has good structural properties, is highly adjustable in important structural parameters such as surface area, pore volume, and average pore size, and retains additional metal sites and acid / alkaline sites, and can be used in CO2 adsorption, significantly improving the adsorption amount of CO2.
[0007] To this end, the first aspect of the present invention provides a method for preparing a MOF material, comprising the following steps:
[0008] preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor;
[0009] preparing a second mixed solution containing a metal salt and a linker;
[0010] The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material;
[0011] The regulator includes at least one of a carboxylic acid and a carboxylate.
[0012] The present invention prepares MOF materials based on a first mixed solution, wherein the first mixed solution includes three different molecules. During the synthesis process, the three molecules play multiple active roles under different temperature conditions, such as acting as pore expanders, structure directing agents and additional ligand sources, thereby obtaining MOF materials with better structural properties. The preparation method is highly adjustable in important structural parameters such as surface area, pore volume, and average pore size, while retaining additional metal sites and acid / alkaline sites, which can be used for CO2 adsorption and significantly improve the adsorption amount of CO2.
[0013] According to an embodiment of the present invention, the neutral ligand includes one of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate.
[0014] According to an embodiment of the present invention, the hydrogen bond acceptor includes one of choline chloride, glycine, choline fluoride, acetylcholine chloride, and choline nitrate.
[0015] According to an embodiment of the present invention, the hydrogen bond donor includes one of urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid.
[0016] According to an embodiment of the present invention, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:1.
[0017] According to an embodiment of the present invention, the metal salt includes at least one of zirconium chloride, zinc nitrate, cupric acetate and ferric chloride.
[0018] According to an embodiment of the present invention, the linking agent includes at least one of phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and tricarboxylic acid.
[0019] According to an embodiment of the present invention, the mass ratio of the metal salt to the connector is (1-2):(0.5-0.8).
[0020] According to an embodiment of the present invention, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100).
[0021] According to an embodiment of the present invention, the temperature of the heat treatment is 120-140°C.
[0022] According to an embodiment of the present invention, the heat treatment time is 18-24 hours.
[0023] The second aspect of the present invention provides a MOF material, which is obtained according to the preparation method described in the first aspect. Thus, a MOF material with good structural performance is obtained, which has high adjustability in important structural parameters such as surface area, pore volume, average pore size, etc., while retaining additional metal sites and acid / alkaline sites, and can be used in CO2 adsorption, significantly improving the adsorption amount of CO2.
[0024] The third aspect of the present invention provides the use of the MOF material obtained by the preparation method described in the first aspect or the MOF material described in the second aspect in CO2 adsorption. Because the aforementioned MOF material has good structural properties and retains additional metal sites and acid / alkaline sites, the adsorption amount of CO2 can be significantly increased, which is nearly 300% higher than that of the traditional UiO-66 material.
[0025] The fourth aspect of the present invention provides a CO2 adsorbent, which comprises the MOF material obtained according to the preparation method described in the first aspect or the MOF material described in the second aspect. Thus, the CO2 adsorbent has good adsorption properties.
[0026] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0028] Figure 1 The overall structural mechanism diagram of the MOF material constructed in the present invention is shown;
[0029] Figure 2 The pore size distribution curves of the MOF material synthesized using different amounts of the first mixed solution added in Example 1 of the present invention are shown. The red, black, green, and blue curves correspond to 1 mL, 2 mL, 3 mL, and 5 mL of the first mixed solution added, respectively;
[0030] Figure 3 The scanning electron microscope images of the MOF material synthesized with the aid of the first mixed solution with different addition amounts in Example 1 of the present invention are shown. The amount of the first mixed solution used in Figures a and b corresponds to 1 mL; the amount of the first mixed solution used in Figures c and d corresponds to 2 mL; the amount of the first mixed solution used in Figures e and f corresponds to 3 mL; the amount of the first mixed solution used in Figures g and h corresponds to 5 mL;
[0031] Figure 4The transmission electron micrographs of the metal organic framework material synthesized by conventional methods and the mesoporous metal organic framework material synthesized by using different amounts of the first mixed solution added in Example 1 of the present invention are shown. Among them, Figure a is a transmission electron micrograph of the UiO-66 material synthesized by conventional methods; Figure b is a transmission electron micrograph of the metal organic framework material obtained by adding 1 mL of the first mixed solution, showing a micro-mesoporous mixed state; Figure c is a metal organic framework material with a micro-mesoporous structure configuration, and the pore size of the structure is less than 2 nm; Figures d and e are transmission electron micrographs of the metal organic framework material obtained by adding 5 mL of the first mixed solution, showing a mesoporous state; Figure f is the structure configuration of the mesoporous metal organic framework material after using the first mixed solution, and the pore size of the structure is greater than 2 nm; Figures g, h, and i are transmission electron micrographs of the mesoporous metal organic framework material obtained by adding 2 mL, 3 mL, and 5 mL of the first mixed solution, respectively;
[0032] Figure 5 The graph shows the result of the CO2 adsorption-desorption experiment of relineMg@UiO-66 in Example 4 of the present invention. DETAILED DESCRIPTION
[0033] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0034] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0036] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0037] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0038] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0039] According to an embodiment of the present invention, a first aspect of the present invention provides a method for preparing a MOF material, comprising the following steps:
[0040] preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor;
[0041] preparing a second mixed solution containing a metal salt and a linker;
[0042] The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material;
[0043] The regulator includes at least one of a carboxylic acid and a carboxylate.
[0044] The first mixed solution includes three different molecules, which play multiple active roles in the preparation process, such as pore expander, structure director and additional ligand source. As the synthesis process proceeds, the hydrogen bond donor undergoes a hydrolysis reaction and a precipitation reaction with the neutral ligand. The resulting precipitate can be decomposed into metal oxides in subsequent heat treatment or washed away with a solvent, leaving a pore structure with a pore size of 17nm-31nm in the material. In this case, the first mixed solution plays the role of a pore expander.
[0045] In addition, due to the low water content in the hydrolysis reaction, the surface tension of the material with a hierarchical porous structure is low, so that its porous structure can be formed quickly. In the preparation process, there are also limiting conditions, that is, as the water content increases, the nucleation reaction rate decreases, but the diffusion rate of the hydrolysis reaction and the overall system increases. Therefore, the morphology of the hierarchical porous material from nanoparticles to one-dimensional structures (such as nanowires and nanorods) with high catalytic activity can be controlled by the first mixed solution. In this case, the first mixed solution plays the role of a structure-directing agent.
[0046] In addition, since the first mixed solution is a neutral ligand, it is usually combined with the metal site of the material as a complete whole. The first mixed solution can provide open metal sites and pores as a template, so after removing the solvent, a large number of pores and open metal sites with more stable properties can be formed in the mesoporous material. Taking the neutral ligand magnesium nitrate hexahydrate as an example, magnesium ions as additional reactants of the ligand can increase the total pore volume and surface area of the material.
[0047] According to a specific embodiment of the present invention, the types of the neutral ligand, hydrogen bond acceptor, and hydrogen bond donor are not particularly limited, and those skilled in the art may select them according to the circumstances. As some specific examples, the neutral ligand includes but is not limited to magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, cobalt nitrate hexahydrate, etc.; the hydrogen bond acceptor includes but is not limited to choline chloride, glycine, choline fluoride, acetylcholine chloride, choline nitrate; the hydrogen bond donor includes but is not limited to urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid.
[0048] According to a specific embodiment of the present invention, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:1.
[0049] According to a specific embodiment of the present invention, the types of the metal salt and the linker are not particularly limited, and those skilled in the art can select them according to the circumstances. As some specific examples, the metal salt includes but is not limited to zirconium chloride (ZrCl4), zinc nitrate, copper acetate, ferric chloride, etc.; the linker includes but is not limited to phthalic acid (BDC), 2-methylimidazole, 2,5-dihydroxyterephthalic acid, tricarboxylic acid, etc. Among them, tricarboxylic acid should be understood as an organic acid containing three carboxylic acids in its molecular structure, including but not limited to 1,3,5-benzenetricarboxylic acid. When the metal salt is zirconium chloride and the linker is phthalic acid, the synthesis mechanism diagram of the MOF material can be seen in Figure 1 , wherein MGS represents the metal salt coordinated low eutectic solvent, that is, the first mixed solution.
[0050] According to a specific embodiment of the present invention, the preparation of the second mixed solution is not particularly limited, and the second mixed solution can be obtained by dissolving the metal salt and the linker in a solvent. The type of the solvent is not particularly limited, including but not limited to dimethylformamide and the like.
[0051] According to a specific embodiment of the present invention, the mass ratio of the metal salt and the connector is (1-2):(0.5-0.8). As some specific examples, the mass ratio of the metal salt and the connector may be 1:0.5, 1:0.8, 1.5:0.5, 1.7:0.8, 2:0.5, 2:0.8, etc.
[0052] According to a specific embodiment of the present invention, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100. As some specific examples, the volume ratio of the first mixed solution, the regulator and the second mixed solution is 1:1:50, 1:1:75, 1:5:100, 2:7:75, 3:7:100, 5:10:100, etc.
[0053] According to a specific embodiment of the present invention, the regulator includes at least one of carboxylic acid and carboxylate, as some specific examples, including but not limited to formic acid, formates, propionates, etc. The regulator will generate connection defects on the surface of the MOF material and help the first mixed solution to establish additional connections with the metal nodes.
[0054] According to a specific embodiment of the present invention, the temperature and time of the heat treatment are not particularly limited, and those skilled in the art may select them according to the circumstances. As some specific examples, the temperature of the heat treatment is 120-140°C; the time of the heat treatment is 18-24h.
[0055] According to a specific embodiment of the present invention, the method for preparing the MOF material further includes: mixing the second mixed solution with a regulator and the first mixed solution, and obtaining the MOF material through heat treatment, washing, activation and drying.
[0056] Specifically, the washing method is not particularly limited, and washing can be performed by ethanol or dimethylformamide.
[0057] Specifically, the activation method is not particularly limited, and the sample can be placed in acetone to remove the suspension solvent and activate the product at the same time. Usually after the MOF material synthesis process is completed, some unreacted metal ions and organic linking molecules will remain in its structure. In order to remove the unreacted organic linking molecules, acetone can be used to activate the final MOF product. After activation, it can be washed with methanol and then dried to obtain the MOF material.
[0058] According to an embodiment of the present invention, the second aspect of the present invention provides a MOF material, which is obtained according to the preparation method described in the first aspect. Thus, a MOF material with good structural performance is obtained, which has high adjustability in important structural parameters such as surface area, pore volume, average pore size, etc., while retaining additional metal sites and acid / alkaline sites, and can be used in CO2 adsorption, significantly improving the adsorption amount of CO2.
[0059] According to an embodiment of the present invention, the third aspect of the present invention provides the use of the MOF material obtained by the preparation method described in the first aspect or the MOF material described in the second aspect in CO2 adsorption. Because the aforementioned MOF material has good structural properties and retains additional metal sites and acid / alkaline sites, the adsorption amount of CO2 can be significantly increased, which is nearly 300% higher than the adsorption amount of the traditional UiO-66 material. At the same time, through the cyclic CO2 adsorption-desorption experiment, it is also confirmed that the material synthesized using the above scheme has good stability and cycle performance.
[0060] According to an embodiment of the present invention, the fourth aspect of the present invention provides a CO2 adsorbent, comprising the MOF material obtained according to the preparation method described in the first aspect or the MOF material described in the second aspect. Thus, the CO2 adsorbent has good adsorption capacity.
[0061] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0062] Example 1
[0063] In this embodiment, different volumes of the first mixed solution are used to synthesize the MOF material, as follows:
[0064] (1) Magnesium nitrate hexahydrate (Mg(NO3)3·6H2O), choline chloride and urea were added to a beaker in a molar ratio of 1:2:1, and placed in an oven preheated to 100°C to allow them to stand until they become liquid. The three liquids were mixed on a magnetic stirrer, and then the solution was heated to a clear and transparent liquid without any bubbles. Thus, a magnesium-based coordination low eutectic solvent (i.e., the first mixed solution) was prepared and named relineMg;
[0065] (2) dissolving 1.06 g of zirconium chloride and 0.67 g of phthalic acid in 50 mL of dimethylformamide at room temperature, and stirring on a magnetic stirrer for 10 min to obtain a second mixed solution;
[0066] (3) adding 5 mL of formic acid to the second mixed solution, stirring for 10 min, and ultrasonically treating for 30 min to ensure that all components are completely and evenly distributed in the solution;
[0067] (4) 1 mL, 2 mL, 3 mL, and 5 mL of relineMg were added dropwise to the mixed solution, stirred on a magnetic stirrer for another 30 min, and ultrasonically treated for 45 min to completely disperse the added components;
[0068] (5) The mixture was placed in a 100 mL Teflon-lined autoclave and heated to 120 °C for 24 h;
[0069] (6) After the reaction is completed, the mixture is washed several times with hot ethanol and then washed several times with hot dimethylformamide solvent;
[0070] (7) The sample was placed in 30 mL of acetone and allowed to stand overnight to remove the suspended solvent and activate the product. After activation, it was washed with methanol three times and dried in vacuum at 80 °C overnight to obtain the mesoporous catalytic material relineMg@UiO-66 synthesized with different concentrations of relineMg.
[0071] The prepared MOF materials were named relineMg x1 @UiO-66, relineMg x2 @UiO-66, relineMg x3 @UiO-66, relineMg x5 @UiO-66, where x1 = 1 mL relineMg, x2 = 2 mL relineMg, and so on.
[0072] In addition, the UiO-66 metal organic framework material (hereinafter referred to as UiO-66) was prepared by conventional methods, specifically: 0.67 g of phthalic acid and 1.06 g of ZrCl4 were dissolved in 50 mL of dimethylformamide and 5 mL of formic acid. Stir on a magnetic stirrer for 10 minutes and then ultrasonically disperse for 30 minutes. After ultrasonic treatment, the mixture was placed in a 100 mL autoclave, heated to 120 ° C, and kept for 24 hours. After the product was cooled to room temperature, it was washed three times with dimethylformamide. In order to activate the sample and remove unreacted dimethylformamide from its structure, the white solid powder was placed in 30 ml of acetone overnight, then washed several times with methanol and dried under vacuum at 80 ° C.
[0073] According to the BJH pore size distribution calculation method, the mesopore size distribution curves of relineMg@UiO-66 synthesized at different relineMg addition amounts are shown in Figure 2 As shown in the figure, it can be seen that the mesopore diameters are centered at 17.4nm, 17.58nm, 30.58nm and 31.17nm respectively. As the amount of relineMg added increases, the crystal size decreases and a large micro-mesoporous structure is formed, which is consistent with the SEM ( Figure 3 ) and transmission electron microscopy ( Figure 4 ) are consistent with the observation results of the conventional method. Among them, UiO-66 synthesized by conventional method presents a regular octahedral morphology with an average particle size of 400nm-500nm. When the amount of relineMg added increases from 1mL to 5mL, the crystal size becomes smaller, and the mesopore size and pore volume become larger. Therefore, the embodiment of the present invention can assist in the synthesis of a metal organic framework with a mesoporous structure by adjusting the amount of relineMg added, and the mesopore size can be adjusted.
[0074] At the same time, the structural porosity parameters of relineMg@UiO-66 can be calculated, as shown in Table 1. It can be seen that all structural parameters of the material are related to the amount of relineMg added. x5 The total specific surface area of @UiO-66 increased by 2.4 times, the average pore size increased by 2.5 times, and the average pore volume increased by 5 times. This material with a high specific surface area, large pore volume and mesoporous structure is a very effective CO2 adsorbent.
[0075] Table 1
[0076]
[0077] Example 2
[0078] This embodiment uses different neutral ligands to prepare mesoporous metal-organic framework UiO-66 materials with different metal nodes. The preparation method is different from that of Example 1 only in that magnesium nitrate hexahydrate is replaced by zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate, respectively. The obtained first mixed solutions are named relineZn, relineCu, and relineCo, respectively, and the obtained mesoporous UiO-66 materials are named relineZn@UiO-66, relineCu@UiO-66, and relineCo@UiO-66, respectively.
[0079] The synthesized material was subjected to PXRD (powder X-ray diffraction) analysis and BET (specific surface area) analysis, and its specific surface area, total pore volume and pore size are shown in Table 2. It can be seen that the mesoporous UiO-66 materials of the three different metal nodes also have a mesoporous structure. This shows that the above implementation method is not limited to magnesium as a metal source, and different metal nodes can also be used to construct the mesoporous structure of the MOF material. The mesopore size and porosity properties of different metal salts used for the auxiliary synthesis of mesoporous MOF materials are Cu>Zn>Co.
[0080] Table 2
[0081] Material <![CDATA[BET specific surface area (m 2 g -1 )]]> Average pore size (nm) <![CDATA[Total pore volume (ccg -1 )]]> UiO-66 918 2.24 0.60 relineCo@UiO-66 1194.29 6.74 2.01 relineCu@UiO-66 1254.06 7.39 2.31 relineZn@UiO-66 1071.72 7.11 1.90
[0082] Example 3
[0083] The mesoporous metal organic framework material relineMg@MOF-808 is prepared by the method provided by the present invention, as follows:
[0084] (1) This step is the same as step (1) in Example 1 to obtain relineMg;
[0085] (2) At room temperature, 1.49 g of 1,3,5-benzenetricarboxylic acid was mixed with 50 mL of dimethylformamide and stirred on a magnetic stirrer until the mixture was uniform;
[0086] (3) Add 2.16 g zirconium chloride and 7 mL formic acid into 25 mL dimethylformamide and stir at room temperature until the mixture is uniform;
[0087] (4) The solutions obtained in step (1) and step (3) were mixed and stirred on a magnetic stirrer for 20 min. At the same time, different amounts of relineMg were added dropwise under continuous stirring. Ultrasonic treatment was performed again for 45 min to completely disperse the added components;
[0088] (5) Place the mixture in a 100 mL Teflon-lined autoclave and heat to 110 °C for 48 h;
[0089] (6) After the reaction is completed, the mixture is washed with hot ethanol and water several times, centrifuged at 1000 rpm for 5 min, collected and washed with hot dimethylformamide;
[0090] (7) The sample was placed in acetone overnight to further activate the product. After activation, it was washed with methanol and dried in vacuum at 80 °C overnight to obtain the mesoporous MOF-808 material, named relineMg@MOF-808.
[0091] After synthesis, this embodiment has the same crystal structure as its parent MOF-808, and has a mesopore size of mainly 13nm. The structural porosity parameters (total specific surface area, average pore size, total pore volume) of the mesoporous MOF-808 material synthesized using different amounts of relineMg are shown in Table 3. It can be seen that the variation trend of its structural parameters such as surface area, average pore size, and total pore volume is very similar to that of relineMg@UiO-66. At the same time, this embodiment also shows that the method provided by the present invention is a general method, which is generally applicable to the construction of different series of mesoporous metal organic framework materials with high specific surface area and pore volume.
[0092] Table 3
[0093] Material <![CDATA[BET specific surface area (m 2 g -1 )]]> Average pore size (nm) <![CDATA[Total pore volume (ccg -1 )]]> <![CDATA[relineMg x1 @MOF-808]]> 1455.80 4.22 1.53 <![CDATA[relineMg x2 @MOF-808]]> 1526.78 5.95 2.27 <![CDATA[relineMg x3 @MOF-808]]> 1634.56 5.51 2.25 <![CDATA[relineMg x5 @MOF-808]]> 2173.14 4.36 2.37
[0094] Example 4
[0095] This example tests the CO2 adsorption performance of relineMg@UiO-66, as follows:
[0096] The CO2 adsorption capacity of the synthesized relineMg@UiO-66 material was tested. For the five MOF materials synthesized in Example 1, their CO2 capture performance under 25°C nitrogen atmosphere (CO2 / N2=15% / 85%, with N2 as the balance gas) and 0.15 bar CO2 pressure was tested. x1 @UiO-66, relineMg x2 @UiO-66, relineMg x3 @UiO-66, relineMg x5 The adsorption capacity of @UiO-66 for CO2 is 39.05mg / g, 63.23mg / g, 67.33mg / g, 69.97mg / g, and 84.65mg / g, respectively. This indicates that in the process of synthesizing mesoporous MOF materials, increasing the amount of metal salt coordinated low eutectic solvent can improve the adsorption performance of CO2, and the adsorption performance can be increased by up to 216%.
[0097] In addition, the current common MOF materials and the relineMg synthesized in Example 1 were compared under the same temperature and pressure conditions. x5 The CO2 adsorption performance of @UiO-66 is shown in Table 4. Due to its higher surface area, total pore volume, larger pore size and the presence of nitrogen atoms in its pore structure, it can be considered that the improvement in CO2 adsorption capacity is the result of physical and chemical adsorption within the pores.
[0098] Table 4
[0099] MOF material name <![CDATA[CO2 adsorption capacity (mg / g)]]> <![CDATA[relineMg x1 @UiO-66]]> 63.23 <![CDATA[relineMg x2 @UiO-66]]> 67.33 <![CDATA[relineMg x3 @UiO-66]]> 69.97 <![CDATA[relineMg x5 @UiO-66]]> 84.65 UiO-66 39.05 MOF-177 4.84 MIL-101 14.08 MOF-5 7.48 MAF-66 55.01 NJU-Bai7 80.09 PCN-88 30.36 Cu-BTC 45.77
[0100] The performance of the adsorbent is evaluated not only by its one-time enhanced adsorption capacity, but also by its performance in long-term adsorption-desorption cycles. Therefore, a cyclic CO2 adsorption-desorption experiment was performed in this example, and 10 consecutive adsorption-desorption cycles were performed to confirm the stability of relineMg@UiO-66, as shown in Figure 2. Figure 5 As shown. The results show that at 25°C and 0.15 bar CO2 partial pressure, 1.4 mmol / g CO2 (61.62 mg / g CO2) was adsorbed, reaching 157% of the equilibrium CO2 adsorption capacity, and it can be completely desorbed at 150°C. In 10 consecutive cycles, the adsorption and desorption performances were completely restored and maintained, with a retention rate of 94.8%, which shows that the mesoporous MOF material synthesized by the synthesis method proposed in the present invention has good regeneration performance.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 1 is that magnesium nitrate hexahydrate is not added in step (1), thereby obtaining reline x5 @UiO-66, and then the CO2 adsorption performance of the material was tested. The specific test method was the same as in Example 4, and the reline x5 @UiO-66 has an adsorption capacity of 51.76 mg / g for CO2. The results show that this preparation method cannot effectively improve the adsorption performance of CO2. The reason is that this preparation method does not add neutral ligands, no additional connection sites are generated, the surface area of the prepared MOF material does not change, and it cannot provide additional open metal sites on the surface of the MOF material, thereby failing to improve the adsorption of CO2.
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0104] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a MOF material, characterized in that: The following steps are involved: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor; preparing a second mixed solution containing a metal salt and a linker; The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material; The regulator includes at least one of a carboxylic acid and a carboxylate.
2. The preparation method according to claim 1, characterized in that: The neutral ligand includes one of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate; Optionally, the hydrogen bond acceptor comprises one of choline chloride, glycine, choline fluoride, acetylcholine chloride, and choline nitrate; Optionally, the hydrogen bond donor comprises one of urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:
1.
4. The preparation method according to claim 1, characterized in that: The metal salt includes at least one of zirconium chloride, zinc nitrate, copper acetate and ferric chloride.
5. The preparation method according to claim 1, characterized in that: The linking agent includes at least one of phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and tricarboxylic acid.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the metal salt to the linker is (1-2):(0.5-0.8); Optionally, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100).
7. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 120-140°C; Optionally, the heat treatment time is 18-24 hours.
8. A MOF material, characterized in that: The MOF material is obtained according to the preparation method according to any one of claims 1-7.
9. Use of the MOF material obtained by the preparation method according to any one of claims 1 to 7 or the MOF material according to claim 8 in CO2 adsorption.
10. A CO2 adsorbent, characterized in that: It includes the MOF material obtained according to the preparation method according to any one of claims 1 to 7 or the MOF material according to claim 8.
Citation Information
Patent Citations
Method of synthesizing micropore SOD type zeolite imidazolate frameworks by ionothermal method
CN103570752A
Method for synthesizing micropore ZNI-type zeolite imidazole skeleton species by ionothermal process
CN103570767A
Hierarchical porous zeolite imidazate skeletal material, and preparation method thereof
CN110105580A
Green synthesis method of Co-based MOF material
CN117843985A
Adsorption and release of nitric oxide in metal organic frameworks
US20100239512A1
Cited By
Bimetal organic framework electrode material based on eutectic solvent and preparation method and application thereof
CN120398211A